Optic-nerve compression by the internal carotid artery as a cause of “unexplained: optic atrophy - Richard C. Kho, MD (Philippine Journal of Ophthalmology)
Objective: To present a case of bilateral optic neuropathy secondary to optic-nerve compression by the internal carotid artery (ICA).